2020
DOI: 10.3390/plants9111430
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizas Regulate Photosynthetic Capacity and Antioxidant Defense Systems to Mediate Salt Tolerance in Maize

Abstract: Salt stress inhibits photosynthetic process and triggers excessive formation of reactive oxygen species (ROS). This study examined the role of arbuscular mycorrhizal (AM) association in regulating photosynthetic capacity and antioxidant activity in leaves of two maize genotypes (salt-tolerant JD52 and salt-sensitive FSY1) exposed to salt stress (100 mM NaCl) in soils for 21 days. The leaf water content, chlorophyll content, and photosynthetic capacity in non-mycorrhizal (NM) plants were decreased by salt stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Similar findings were reported in other plants in which salinity induced changes [ 44 , 45 ]. It is known that reduction in the chlorophyll content under salt stress reduces light reactions and electron transport in PS II from primary to secondary acceptor [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported in other plants in which salinity induced changes [ 44 , 45 ]. It is known that reduction in the chlorophyll content under salt stress reduces light reactions and electron transport in PS II from primary to secondary acceptor [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…AMF is considered to promote plant growth and salinity tolerance (Evelin et al, 2019). The AMF improved antioxidant systems in stress plants have been reported in Wheat (Abdel Latef, 2010) and Maize (Wang et al, 2020). Additionally, it can alleviate salt stress by decreasing oxidative stress in plants and improved concentrations of osmolytes such as proline, polyamines, and glycine betaine (Frosi et al, 2018); enhancing lipids and proteins, quenching free radicals, and buffering cellular redox potential under salinity stress (Yang et al, 2008); improving in photosynthetic activity (Wang et al, 2022) due to mycorrhizal colonization in plants are limited the Na + transport (Zhu et al, 2010), energizing carbohydrate transport and metabolism (Kaschuk et al, 2009), increasing the leaf area and higher stomatal conductance and consequently better assimilation CO 2 due to improving water situation in plants (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cayún et al [ 18 ] reported similarities between potato plants inoculated with AMF and control plants with respect to the photosynthetic rate and an increase in the concentration of chlorophyll in AMF-inoculated samples. AMF inoculation reportedly increases enzymatic antioxidant activity in corn, olive, and potato leaves and roots [ 19 , 20 , 21 ]. AMF root colonisation also causes changes in root exudates, increasing the contents of low-molecular-weight organic acids (LMWOAs) secreted by maize and potato plants [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%